Periprostatic adipose tissue: A heavy player in prostate cancer progression. (February 2020) - Estève, David; Roumiguié, Mathieu; Manceau, Cécile; Milhas, Delphine; Muller, Catherine
Abstract: Prostate is surrounded by a specific fat depot called periprostatic adipose tissue (PPAT) that contributes through paracrine mechanisms to prostate cancer (PCa) progression. Like other white adipose tissues, PPAT stores lipids and is an endocrine organ. However, PPAT is still poorly characterized. Nevertheless, current evidence highlights that soluble factors secreted from PPAT might promote PCa aggressiveness and local dissemination. In addition, the ability of adipocytes to provide lipids to tumor cells participates in tumor aggressiveness. The secretory and metabolic profile of PPAT is modified by obesity, a state associated with greater occurrences of aggressive diseases. Beyond obesity, the excessive accumulation of PPAT, independently of the ponderal status of the patients, is an emerging risk factor in aggressive diseases. Characterization of the role of human PPAT on PCa progression will undoubtedly provide, in the near future, new therapeutic strategies and new risk stratification factors in PCa. Highlights: The periprostatic adipose tissue contributes through paracrine mechanisms to prostate cancer (PCa) progression. Periprostatic adipose tissue inflammation leads to the release of cytokines that affect PCa aggressiveness. Lipids released from periprostatic adipose tissue are taken up by tumor cells and stimulate tumor aggressiveness. Periprostatic adipose tissue abundance, dissociated from ponderal status, is an emerging factor of PCa aggressiveness.